La tributación del comercio electrónico - Cerna García, María Eugenia Del Carmen (2013)
Today, as a result of the phenomenon of globalization and the modern information society, there has been an unprecedented rise and development of international trade, specifically, of that trade developed through modern information technology and communication. Well, this new phenomenon requires us to perform an analysis and rethinking of legal matters related to this area of knowledge, being in our interest, the matter related to taxation, in both, crisis legal concepts hitherto conceived, regarding the current tax system and other international taxation own; arising therefore, the need to rethink the traditional legal concepts, or to create new legal frameworks that conform to this new reality, and thus deal challenges to the advancement of technology. The taxation of electronic commerce is a broad topic, but the purpose of our research is to analyze the implementation of the General Sales Tax to this new form of commerce, as well as to present the progress that has been achieved in the world regarding this matter, and formulate the parameters that should guide the indirect taxation of electronic commerce in our country